Child Cyber Grooming Sebagai Bentuk Modus Baru Cyber Space Crimes - Anjeli Holivia; Teguh Suratman (University of Merdeka Malang, 2021)
The development of technology and communication in the current era of globalization is very fast. Along with this, new innovations in crime were born. Currently, the use of the internet in cyberspace is a necessity in any activity. Not only adults who use internet access but children also know and use the internet. One of them is the use of social media, in order to make it easier to communicate and interact without having to meet face to face. Apart from having a positive impact on its users, social media alsohas a negative impact. One form of crime that is currently happening is Child Cyber Grooming, which is a crime of decency against children through social media. The mode of this crime is that the perpetrators will approach, seduce and commit tricks through social media. This study uses juridical-empirical legal research methods that use legal materials in the form of statutory regulations and legal facts that occur in the field. The result of this research is that the legal measures that can be taken in handling the Child Cyber Grooming case are preventive and repressive measures. Another effort used to overcome this type of crime is the involvement of various elements of society, especially parents, who must be wise in monitoring the use of social media so as not to become trapped in sexual crimes known as Child Cyber Grooming.